Cutting force and tool life models in end milling titanium alloy ti-4al-4v with thermally-assisted machining - Ginta, Turnad Lenggo; Amin, A. K. M. Nurul (Trigin Publisher, 2012)

(untitled)
Titanium and its alloys are known as difficult-to-cut material due to some circumstances, such as high chemical reactivity, low thermal conductivity, low modulus of elasticity, and high strength at elevated temperature. Furthermore, higher cutting force and lower tool life in machining of these alloys are very common. An approach to reduce the cutting force and increase the tool life is to employ thermally-assisted machining. The working piece surface was heated up until a certain temperature just before cutting. This paper presents an approach to establish mathematical models for cutting force and tool life in end milling of titanium alloy Ti–6Al–4V using PCD inserts under thermally-assisted machining using high frequency induction heating. Response surface methodology (RSM) was employed in developing the cutting force and tool life models in relation to primary cutting parameters such as cutting speed, feed, and preheating temperature. Design-expert software was applied to establish the first-order and the second-order model and develop the contours. The adequacy of the predictive model was verified using analysis of variance (ANOVA) at 95% confidence level